1990
DOI: 10.1093/ajcn/52.4.731
|View full text |Cite
|
Sign up to set email alerts
|

Diet of second-generation Japanese-American men with and without non-insulin-dependent diabetes

Abstract: Second-generation Japanese-American (Nisei) men have rates of non-insulin-dependent diabetes mellitus four times higher than men in Japan, suggesting a role for environmental factors in the etiology of this disease. Dietary intake was assessed for 229 Nisei men with diabetes (DM, n = 78), impaired glucose tolerance (IGT, n = 72), and normal glucose tolerance (NGT, n = 79). The diet of Nisei men with DM compared with men with IGT or NGT was similar in kilocalories but higher in fat and protein. Absence of diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 27 publications
2
49
0
3
Order By: Relevance
“…High prevalence rates of type 2 diabetes and associated diseases in Japanese migrants living in the Americas (8 -11) suggest that the exposure to a different lifestyle exacerbated an inherent tendency to accumulate fat and develop diabetes (12). Our group and others reported that dietary changes, such as an increase in animal fat intake and reduction in complex carbohydrates, were imposed by immigration (12)(13)(14)(15).…”
Section: Diabetes Care 28:1779 -1785 2005mentioning
confidence: 96%
See 1 more Smart Citation
“…High prevalence rates of type 2 diabetes and associated diseases in Japanese migrants living in the Americas (8 -11) suggest that the exposure to a different lifestyle exacerbated an inherent tendency to accumulate fat and develop diabetes (12). Our group and others reported that dietary changes, such as an increase in animal fat intake and reduction in complex carbohydrates, were imposed by immigration (12)(13)(14)(15).…”
Section: Diabetes Care 28:1779 -1785 2005mentioning
confidence: 96%
“…High prevalence rates of type 2 diabetes and associated diseases in Japanese migrants living in the Americas (8 -11) suggest that the exposure to a different lifestyle exacerbated an inherent tendency to accumulate fat and develop diabetes (12). Our group and others reported that dietary changes, such as an increase in animal fat intake and reduction in complex carbohydrates, were imposed by immigration (12)(13)(14)(15).Animal studies suggested that the type of fat in diet may affect insulin sensitivity by changing the fatty acid composition of membrane lipids (16). In humans, a detrimental effect of saturated fat or a benefit of polyunsaturated fat is controversial (3,(17)(18)(19).…”
mentioning
confidence: 99%
“…14,15,45 In summary, this study shows that adverse patterns of fatty acids and DA are already associated with overweight and insulin resistance before adulthood. Results of observational and clinical studies conducted in humans have shown that a diet high in total or saturated fat is associated with abnormal glucose concentrations 3,46,47 or insulin resistance, 3,48 whereas diets enriched in monounsaturated fat 39,49 or Serum fatty acids and CVD risk factors in overweight adolescents LM Steffen et al linoleic acid 50 improve insulin sensitivity. Beneficial changes in the CE fatty acid profile and DA ratios were related to improved insulin sensitivity in a population at risk for type 2 diabetes.…”
Section: Monounsaturated Fatty Acidsmentioning
confidence: 99%
“…The modified FFQ followed a format adapted from Tsunehara et al 33 with Japanese-Americans, quantifying the intake of 177 foods in the previous two months. Chemical composition of the diet was calculated using a software program developed by the Health Information Technology Department, EPM/UNIFESP (Anção MS, Cuppari L, Tudisco ES, Draibe SA, Sigulem D. Nutritional Support Program, version 2.5).…”
Section: Data Collectionmentioning
confidence: 99%